Accountability in Collaborative Governance at the Corporate Social and Environmental Responsibility Forum in Maros Regency - Firliana, Nurannisa; Ahmad, Badu; Hasniati, ‎ (KnE Social Sciences, 2025)
Accountability in collaborative governance is one of the key factors for successful collaboration. This study aims to explore accountability in collaborative governance at the Corporate Social and Environmental Responsibility Forum (TSLP) in Maros Regency. The research method used is a descriptive qualitative approach, this study collects data through in-depth interviews, participatory observation, and document analysis regarding corporate social and environmental responsibility and collaborative activities at the TJSLP Forum in Maros Regency. The results of the study indicate that the TSLP Forum in Maros Regency has succeeded in providing a transparent information platform regarding the allocation and impact of the Corporate Social and Environmental Responsibility (TSLP) program, although the distribution of information is not evenly distributed. There are formal and informal discussion forums between stakeholders, namely local governments, companies, and communities, but they are not fully inclusive, because community groups tend to be less involved. Regarding the consequences, the evaluation and follow-up mechanisms for the CSR program are still limited, so that supervision of program implementation is not optimal. Therefore, although there are efforts made to improve accountability through discussion, information, and consequences in collaborative CSR governance in Maros Regency, it still requires strengthening in various aspects of accountability in collaboration in the TJSLP forum.